ANALISIS KUALITAS AIR DAN DAYA TAMPUNG BEBAN PENCEMARAN SUNGAI PESANGGRAHAN DI WILAYAH PROVINSI DKI JAKARTA - Veybi Djoharam; Etty Riani; Mohamad Yani (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
Pesanggrahan River has important role and function to support human life and ecosystem existing in river area. Daily human activities that utilize river water and then dispose the sewage/waste into Pesanggrahan River can decrease the air quality. This research aims to analyzed the water quality condition of Pesanggrahan River based on physical and chemical water river factors. The analysis was conducted on eight observation points along the Pesanggrahan River in DKI Jakarta Province by testing the air pollution parameters comparing it to the air quality standard of Governmental Regulation No. 82/2001 on Air Quality Management and Air Pollution Control for Class II and Jakarta Governor Regulation No. 582/1995 on the Establishment of the Allocation and Quality Standards of River Water/Raw Water Agency of Liquid Waste Quality Standard in the Special Capital Region of Jakarta for Group C. The parameters observed in this study are 18 and 6 overall physical parameters (temperature and TSS) and parameters chemical (pH, DO, BOD, and COD). Determination of water quality status using pollution index method compared with air quality standard Governmental Regulation No. 82/2001 class II and Jakarta Governor Regulation No. 582/1995 Group C. The air quality condition of Pesanggrahan River from upstream to downstream at eight points of observation has generally decreased quality according to parameters of TSS, DO, BOD and COD which were not fulfill the quality standard. Based on the status of water quality status of Pesanggrahan River from upstream to downstream has decreased quality with mild to moderate pollutant status.